Survival Strategies of Offline Pickup-Truck Culinary Vendors in the Digital Era: A Qualitative Study in East Ungaran District, Indonesia - Shohib Maulana; Irsal Fauzi (International Forum of Researchers and Lecturers, 2026)
The rapid development of digital technology has significantly transformed business practices in the culinary sector, particularly through online food delivery platforms, social media marketing, and digital payment systems. While many culinary businesses have adopted digital technology to expand their market reach, some small-scale culinary vendors continue to operate using conventional business models. This study aims to analyze the survival strategies employed by offline pickup-truck culinary vendors in the digital era. A qualitative descriptive approach was employed to explore the experiences and business practices of culinary vendors operating without online marketing platforms in East Ungaran District, Semarang Regency, Indonesia. Data were collected through in-depth interviews, observations, and documentation involving one primary informant and two supporting informants selected using purposive sampling. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, supported by MAXQDA software for coding and thematic analysis. The findings indicate that business sustainability is primarily maintained through consistent product quality, preserving food taste, providing friendly customer service, maintaining competitive pricing, and strengthening social relationships with customers. Although the vendors have not adopted digital marketing, they have selectively utilized QRIS as a digital payment method to facilitate transactions. The study concludes that business survival in the digital era is not solely determined by technological adoption but is also strongly influenced by product quality, customer trust, and social capital developed through direct interactions. These findings contribute to the understanding of survival strategies among informal culinary businesses operating outside digital platforms.